Career Decision-Making in Indonesia: Cultural Values among Javanese, Sundanese, and Minangkabau - Noviati, Nur Pratiwi; Kadiyono, Anissa Lestari; Sulastiana, Marina; Lubis, Fitriani Yustikasari (LPPM Universitas 17 Agustus 1945 Samarinda, 2025)
The purpose of this study is to explore the role of ethnic identity and cultural values in the career decision-making process among early-career employees from Javanese, Sundanese, and Minang ethnic groups in Indonesia. The research method used is qualitative with a phenomenological approach. The participants in this study were three early-career employees each representing one ethnicity. Participants were selected purposely and interviewed in depth. Data were analyzed using thematic analysis to identify relevant patterns and themes. The results of the study indicate that internal individual factors and cultural values can have a complex influence on individuals in making career decisions. The value of collectivism is found in the Javanese ethnic with the family philosophy of